Pengaruh Perilaku Konsumen Terhadap Keputusan Pembelian Vegetarian Di Vegetariano Sushi Batam - Serviana, Serviana; Pratama, Tito; Wahyudi, Ilham; Dailami, Dailami (Universitas Pahlawan Tuanku Tambusai, 2024)
This research investigates how consumer behavior influences the purchasing decisions of vegetarian products at Vegetariano Sushi in Batam. The methodology applied is explanatory research with a quantitative approach. Data analysis is conducted using SMART PLS 4 software. The population studied comprises consumers who have visited Vegetariano Sushi Batam, with an uncertain number. Due to uncertainty regarding the population size, the study adopts a Accidental Sampling approach along with the Lemeshow Formula. The findings indicate that consumer behavior significantly impacts the purchasing decisions of vegetarian products at Vegetariano Sushi.